PRE-SERVICE MATHEMATICS TEACHERS’ ALGEBRAIC THINKING IN SOLVING MATHEMATICS PROBLEMS BASED ON ADVERSITY QUOTIENT - Nur Hanifatur Rahmah; Masduki Masduki (FKIP Universitas Muhammadiyah Tangerang, 2023)
Algebraic thinking has an important role in solving mathematics problems. In addition, Adversity Quotient (AQ) is one of the factors that can help students succeed in solving math problems. This study aims to investigate the algebraic thinking skills of pre-service mathematics teachers (PMTs) in solving math problems based on adversity quotient (AQ). This study investigates three components of algebraic thinking, namely generalization, functional thinking, and justification. This research used qualitative approach with a case study method. The subjects were 30 PMTs at one of private universities in Surakarta District, Central Java, Indonesia. Data were collected by the algebraic thinking test, ARP (Adversity Response Profile) questionnaires, and interview protocol. The results showed that climber PMTs were able to demonstrate algebraic thinking activities in the components of arithmetic generalization, functional thinking, and generalization and justification. Camper PMTs were only able to demonstrate algebraic thinking activities in the components of arithmetic generalization and also generalization and justification. Meanwhile, quitter PMTs were unable to demonstrate algebraic thinking activities in all components. It can be concluded that the characteristics of AQ are related to the PMTs’ algebraic thinking abilities